The Effectiveness of Using the Action Learning Method in Increasing Student Learning Motivation in Islamic Religious Education Subjects at State Junior High School 7 Pamekasan - Maulidatul Laily; Moh. Afiful Hair (STIT Attaqwa, 2025)
Student learning motivation in Islamic Religious Education subjects at Pamekasan 7 State Junior High School. To determine the effectiveness of using the Action Learning method and also to determine the increase in learning motivation in Islamic Religious Education subjects. There are two main problems in this research, 1) What is the effectiveness of using the Action Learning method in increasing students' learning motivation in Islamic Religious Education subjects at Pamekasan 7 State Junior High School? 2) What are the supporting and inhibiting factors for using the Action Learning method in increasing students' learning motivation in Islamic Religious Education subjects at Pamekasan 7 State Junior High School? The research method used in this research is a qualitative method where the research results obtained are in the form of descriptive data, the data sources for this research are the school principal, PAI subject teachers, and also students. The data analysis was carried out using a qualitative descriptive method by reducing the data, presenting the data, and verifying the data obtained. The results of the research that the researchers have carried out are that in the learning process an experienced (professional) teacher is needed, in this case an experienced teacher is a teacher who is good at choosing a learning method and the effectiveness of using the Action Learning learning method in increasing students' learning motivation in Islamic Religious Education subjects at Pamekasan 7 State Junior High School which is used by teachers in teaching, is effective because it makes students feel enthusiastic, not bored, and also not bored. This is proven by the students' sense of activity and high levels of enjoyment and enthusiasm in participating in learning and little by little there is improvement, this is proven from the results of observations and interviews with teachers and students. Meanwhile, the supporting factors and inhibiting factors in increasing learning motivation using the Action Learning method, seen from the supporting factors, can also be seen from adequate learning media (facilities and infrastructure), teacher motivation, and high interest in learning from students, while the inhibiting factors are lack of student awareness, students' tiredness, and lack of enthusiasm for learning from students.